Pengembangan Program MATLAB OHM1.m sebagai Media Pembelajaran Hukum Ohm - Ulul Ilmi; Achmad Febrian Erdiansyah; Ahmad Fuad Al Arsyad; Dani Syauqi Sudrajat; Eep Syaifullah Yusuf; Hasip Saifullah; Khaifal Fahrully Khafid Aryadianto (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The research presents an examination of Ohm’s Law in practice through the development of a simple MATLAB-based program named OHM1.m. The program is designed to calculate the electric voltage based on the current and resistance values entered by the user. The program structure consists of a few concise lines of code, including screen clearing, variable initialization, input retrieval, voltage calculation using the equation V = I x R, and formatted result presentation. The analysis shows that the program has several advantages, such as simplicity, interactivity, organized output, and strong relevance to education. Nevertheless, some limitations exist, including the absence of input validation, lack of batch data support, and the unavailability of graphical visualization. Potential enhancements include adding input validation, integrating V–I plotting, supporting vector input, and developing a graphical user interface (GUI). The program execution results are consistent with Ohm’s Law theory, making it an effective learning tool for both Electrical Engineering and Informatics students. Therefore, this program can serve as a foundation before progressing to more complex circuit simulations.